2015
DOI: 10.2174/1874070701509010199
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of an Acidic Protease from Rhizopus stolonifer RN-11

Abstract: Abstract:The present study characterises an acidic protease purified from the Rhizopus stolonifer strain, RN-11. The acidic protease with a 70 kDa molecular weight, was stable within pH 2-4 at temperatures 40-50℃. The temperature and pH value conducive to optimal catalytic activity were pH 2.5 and 50℃, respectively. Treatment with 5 mmol metal ions showed that the acidic protease was activated by Na . It was proposed that the studied acidic protease might represent a previously uncharacterised type of acidic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…respectively. Griffen et al [29] also reported that aspartic protease by F. graminearum had molecular mass of 40 kDa.With respect to results obtained, a similar protein size of 70 kDa on SDS-PAGE was reported by Na and Liang [30].…”
Section: Application Of Proteasesupporting
confidence: 88%
“…respectively. Griffen et al [29] also reported that aspartic protease by F. graminearum had molecular mass of 40 kDa.With respect to results obtained, a similar protein size of 70 kDa on SDS-PAGE was reported by Na and Liang [30].…”
Section: Application Of Proteasesupporting
confidence: 88%
“…On the other hand, NiCl 2 and ZnSO 4 showed an inhibitory effect on the milkclotting activity as compared to the control (Skim-milk only). Similarly, Ca 2+ (El-Tanboly et al, 2013), Na + , K + , Mn 2+ and Ca 2+ (Liu and Huang, 2015) and Ca 2+ , Mg 2+ , Mn 2+ (Kumari et al 2016) and Mn 2+ , Ca 2 (Ahmed et al, 2016) were shown a noticeable effect on enhancing the the activity of milk-clotting enzyme from M. pusillus QM 436, acidic protease from Rhizopus stolonifer, MCE from B. subtilis MTCC 10422 and MCE from B. stearothermophilus, respectively. Whereas the addition of Co 2+ , Cd 2+ and Zn 2+ were found to have an inhibitory effect on the activity of MCE from B. subtilis MTCC 10422 (Kumari et al 2016).…”
Section: Discussionmentioning
confidence: 92%